Agricultural work-related fatalities and injuries in Punjab (India). Issue 5 (6th May 2022) - Lohan, Shiv Kumar; Singh, Prashant; Kumar, Sunil
Abstract : Objective: Analysis of data on monetary compensation and estimating the rate of injuries related to agricultural activities in the state of Punjab. Methods: The primary data were collected from 22 districts of Punjab state for 2012–2015 through Punjab State Agricultural Marketing Board, Mohali. Data were analysed for the nature of health hazards, type of injuries, possible causes and factors of injuries and their gender. Results: During the four consecutive years (2012–2015) an overall 5888 hazards cases related to agricultural activities were reported from the state, out of which 1993 (33.85%) were fatal and 3895 (66.15%) were non-fatal injuries. Among the fatal cases, the leading causes reported were due to electric motors (34.47%), poisoning through snake bites (21.48%), poisoning through pesticide applications with sprayers (19.62%) and crushed under/falling from the tractors and related equipment (13.50%). The annual fatality rate of the state of Punjab was estimated as 14.14 per 100 000 agricultural workers, while the overall injury incidence rate was observed as 39.57 per 100 000 agricultural workers. Conclusions: Majority of agricultural work-related health hazards in Punjab were mainly due to negligence, lack of knowledge/experience, restlessness/sleeplessness, inadequate safety measures, over speed and wrong practices employed by the operator. There is a need for better ergonomic controls, work environments and practices for the prevention of injuries and health hazards related to agricultural activities.